FACTORS THAT INFLUENCE THE SUCCESS OF CONCEPTUAL CHANGE MODEL (CCM) ON COURSE LEARNING OF MATHEMATICS ELEMENTARY - Wijayanti, Rina; Cipta, Dyah Ayu Sulistyaning (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
The Course of Mathematics Elementary School is a course intended toprepare university students to become a math teacher in elementary school.The material in Mathematics Study of Elementary School is Integer andFractional. This case study get in Institute of Teacher Education andEducational Science of Budi Utomo Malang. The author teach this materialwith the Conceptual Change Model. Next we want to know the factors thataffect Conceptual Change Model. The sample was taken from 45 students ofMathematics Education and obtained the conclusion of Process ofconceptual changes variable, Cognitive Conflict and Knowledge of the pasthave significant effect on CCM success in elementary mathematics study, itis proved from the value of p value of the three consecutive variables (0.00;0.001 ; 0.034) these three values are <0.05 (5% error rate / alpha).